Is there any need and scope for improvement in the vector control measures? - Saurabh RamBihariLal Shrivastava; Prateek Saurabh Shrivastava (Wolters Kluwer Medknow Publications, 2019)
Owing to the rapid and unplanned urbanization, varying use of lands, and an exponential rise in trade and global travel, the number of opportunities for a vector contact with humans has significantly increased. In fact, the recent global estimates depict that in excess of four-fifth of the world's population is at risk of at least one or more vector-borne diseases (VBDs). All these factors together justify the need for an urgent and a holistic approach to minimize the incidence and impact of VBDs. Systematic analyses of the existing vector control measures indicate that there is an immense scope to ameliorate the impact of vector control. In conclusion, there is a big-time need for having a collaborative and coordinated response for the containment of VBD worldwide, and thus, all the stakeholders should work together for the achievement of the same.